Open competition or balkanized coexistence? The effects of market segments on Toronto private schools - Roger Pizarro Milian; Scott Davies (Arizona State University, 2017)
For over 25 years, school choice advocates have argued that market competition drives educational organizations to become more differentiated and technically-oriented. However, empirical research has only partially supported this view, observing such outcomes only under certain conditions. To better understand the contingent nature of market effects within education, we draw on sociological and organizational theories that emphasize the 'embeddedness' of economic behavior. We test this idea using data from all private schools in Toronto, Canada, a strategic setting that approximates a 'pure' market by being mostly free of public governance. We find that, net of factors like school size and age, market segment is associated with the presence of a variety of organizational features. In conclusion, we ponder ways that institutional norms and community ties not only buffer schools from market forces, but also, infuse consumer preferences.